2016
DOI: 10.1177/0963947015623360
|View full text |Cite
|
Sign up to set email alerts
|

A comparable comparison? A corpus stylistic analysis of the Italian translation of Julian Barnes’ Il Senso di una Fine and the original text The Sense of an Ending

Abstract: Foregrounding (e.g. Leech, 1965, 1985; Leech and Short, 1981), whereby certain linguistic elements in literary works differ consistently and systematically (Mukařovský, 1958: 44) from norms represented by a particular benchmark, has often been measured using corpus stylistic methods (e.g. Mahlberg, 2013; Stubbs, 2005). While most such studies have focused on works in their original language, this study compares the translation with the original text. More specifically, I explore the stylistic elements identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This is probably because style is an elusive concept in translation studies and, at the same time, stylistic research seems to focus more on literary works in a particular language (Boase-Beier, 2020;Huang, 2015;Lin, 2014). The present study, in line with recent studies on corpus stylistic approaches to translation, for example, Čermáková (2018), Johnson (2016) and Mastropierro (2018), seeks to demonstrate that the approach can systematically identify colour words and their textual patterns as a major stylistic feature of GG and that it can benefit, especially when combined with cognitive perspectives, literary translation, both as a practice and as a scholarly pursuit.…”
Section: Introductionsupporting
confidence: 75%
“…This is probably because style is an elusive concept in translation studies and, at the same time, stylistic research seems to focus more on literary works in a particular language (Boase-Beier, 2020;Huang, 2015;Lin, 2014). The present study, in line with recent studies on corpus stylistic approaches to translation, for example, Čermáková (2018), Johnson (2016) and Mastropierro (2018), seeks to demonstrate that the approach can systematically identify colour words and their textual patterns as a major stylistic feature of GG and that it can benefit, especially when combined with cognitive perspectives, literary translation, both as a practice and as a scholarly pursuit.…”
Section: Introductionsupporting
confidence: 75%
“…He examines whether and how the multitude of implicatures and implicit meanings that characterise Emma ’s dialogues have been reproduced in the Italian TTs. Corpus approaches too have been extensively employed to support the comparative study of translation (see, for example, Mastropierro, 2017; Mastropierro and Mahlberg, 2017; Bosseaux, 2004, 2006; Čermáková, 2015; Čermáková and Fárová, 2010; Johnson, 2016; Winters, 2009, 2010), not only because corpus tools can enhance the comparison of texts but also because they offer a wider range of analytical possibilities unachievable without the help of the computer. The studies mentioned here have confirmed the theorists’ claim that textual alterations are intrinsic features of the translated text, showing with concrete evidence that the act of translating creates a new text, as opposed to copying transparently an existing one.…”
Section: Introductionmentioning
confidence: 99%
“…This inherent contrast to linguistic norms suggests an obvious approach to identify candidates for inclusion – keyword analysis. Keyword analysis, an approach pioneered by Scott (1997), has increasingly been used in corpus stylistics as a means of approaching deviation and thereby foregrounding (Leech and Short, 2007; Mukařovsky, 1958), that is, aesthetically motivated linguistic deviation from a particular norm (Johnson, 2016). The keyword approach is particularly suited to investigating foregrounding because it provides the analyst with a list of wordforms that are found significantly more often in the target text or corpus than in a reference corpus (O’Halloran, 2007; Scott, 1997; Stubbs, 2005).…”
Section: Methodology: Identifying Nadsatmentioning
confidence: 99%